Fairness in supply chain contracts: A laboratory study - Katok, Elena; Pavlov, Valery (Journal of Operations Management, 2013)
AbstractVarious contracts can be designed to coordinate a simple supplier–retailer channel, yet the contracts proposed in prior research and tested in a laboratory setting do not perform as standard theory predicts. The supplier, endowed with all bargaining power, can neither fully coordinate the channel nor extract all of the channel profit. We report on a sequence of laboratory experiments designed to separate possible causes of channel inefficiency. The three causes we consider are inequality aversion, bounded rationality, and incomplete information. It turns out that all three affect human behavior. Inequality aversion has by far the most explanatory power regarding retailers’ behavior. Incomplete information about the retailer's degree of inequality aversion has the most explanatory power in regards to the suppliers’ behavior. Bounded rationality affects both players, but is of secondary importance.